Olympic sports of the future - Stefani, R. (The Sport Journal, 2016)
This paper explores possible future Olympic sports by examining the past. The ancient Olympic Games began in 776 BC with just one running event. Over the centuries, five more Track and Field (Athletics) events were added as well as four other sports with 22 events. These new sports kept the Olympics relevant to the times and interesting enough that the Games survived until 277 AD, At least two emperors competed and became Olympic champions. During the modern Olympic Games though 1992, organizers provided flair by adding non-medal demonstration sports, albeit in a rather haphazard manner, some of which became permanent sports. As the number of events rose to fill the available time period of both the Summer and Winter Olympics, a rather rigid system was used to limit the number of sports. That system had less-than-ideal success in adding new sports, which had to be at the expense of deleting older sports. The International Olympic Committee recently enacted Olympic Agenda 2020, which includes a much more flexible system for adding new sports. Under control of the International Olympic Committee Executive Board, an organizing Committee may request to add medal sports for that Games and that same IOC Committee can add new sports permanently, by modifying the number of events, without necessarily dropping existing sports. This paper examines the recent request by the 2020 Tokyo Organizing Committee as well the complete list of recognized sports from which new sports must be drawn, to gauge the possible types of future Olympic sports.